Overcoming the threat of poverty and social welfare amid the COVID-19 pandemic through sustainable funding sources - Saddam Rassanjani; Risky Novialdi; Nur Saribulan; Dahlawi Dahlawi (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2023)
The COVID-19 outbreak is believed to have slowed economic acceleration in several countries, including Indonesia. Dramatic economic changes affect the country's performance in overcoming poverty and unemployment. This article aims to analyze the social and economic impact of the pandemic. It can be seen that the government, as the holder of the mandate of power, still and will continue to rely on social protection programs in dealing with the social and economic impacts that are currently being faced. The government can expand social security and assistance programs by strengthening collaboration between local authorities and non-state institutions. In addition to social protection, Indonesia, known as a country with a Muslim majority, has a religious instrument called zakat, which is believed to overcome the spike in poverty. Moreover, zakat is also considered a potential instrument to support some countries in achieving SDG goals as long as they are appropriately managed.